Pelaksanaan pendidikan keusahawanan di Malaysia: kesan terhadap aspirasi keusahawanan pelajar - Lope Pihie, Zaidatol Akmaliah; Bakar, Ab. Rahim; Konting, Mohd Majid (Universiti Putra Malaysia Press, 2002)
Realizing the importance of entrepreneurship education in preparing students with opportunities and potentials to choose future careers as entrepreneurs, the Ministry of Education have shown their commitment towards its implementation. The entrepreneurship component was introduced in the living skills subject at the lower secondary school level. Based on this effort, a study is needed to evaluate the effect of this on students' choices of entrepreneurship as a career. About 1336 Form Four students were selected to participate in the study by using the multi-stage random sampling procedure. Findings indicated that students' aspirations are still low. Those who obtained high academic achievement in PMR examination have low entrepreneurial potential and vice versa. There is a significant difference between students' characteristics and potentials between those who choose to be self employed and those who choose working with others. As a whole, students' entrepreneurial attitudes and characteristics are moderately positive. Implications of the study are discussed in the paper to infuse the entrepreneurial spirit among secondary school students.